2012
DOI: 10.1017/s1368980012000742
|View full text |Cite
|
Sign up to set email alerts
|

Impact of orange juice consumption on macronutrient and energy intakes and body composition in the US population

Abstract: Objective: The present study evaluated the contribution of 100 % orange juice (OJ) consumption to the intakes of macronutrients and energy and its impact on body composition. Design: A cross-sectional study was conducted. The main exposure was OJ consumption based on two non-consecutive 24 h diet recalls. Macronutrient and energy intakes and body composition parameters were outcome measures. All statistical analyses were carried out using SAS and SUDAAN statistical software packages to allow for multistage sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 20 publications
(39 reference statements)
2
19
0
Order By: Relevance
“…Importantly, 100% juices contain micronutrients and vitamins which are vital to supporting and maintaining health. In a cross-sectional study among US adults, for example, Pereira et al found that compared with non-consumers, those who consumed 100% fruit juice were leaner and had lower odds of obesity [47] and consumers of 100% orange juice, in particular, have been shown to have lower levels of BMI, waist circumference, and percentage body fat, and lower odds for overweight and obesity compared to non-consumers [16]. The results from the present study are similar to those reported for other 100% fruit juices, with cranberry juice consumers having lower waist circumferences and lower risk of obesity compared to non-consumers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, 100% juices contain micronutrients and vitamins which are vital to supporting and maintaining health. In a cross-sectional study among US adults, for example, Pereira et al found that compared with non-consumers, those who consumed 100% fruit juice were leaner and had lower odds of obesity [47] and consumers of 100% orange juice, in particular, have been shown to have lower levels of BMI, waist circumference, and percentage body fat, and lower odds for overweight and obesity compared to non-consumers [16]. The results from the present study are similar to those reported for other 100% fruit juices, with cranberry juice consumers having lower waist circumferences and lower risk of obesity compared to non-consumers.…”
Section: Discussionmentioning
confidence: 99%
“…Orange juice (and to a lesser extent apple juice) is the most commonly studied 100% juice in the published literature, and the most commonly consumed juice [16,17] in the United States. Importantly, 100% fruit juice does not necessarily have the same negative association with health for children or adults in either cross sectional [16] or longitudinal [18,19] studies.…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate, scientific studies have shown that citrus fruits improve human diets by supplying essential nutrients, including Vitamin C, flavonoids, phenolic compounds, carotenoids, folic acid, pectin, potassium, and dietary fiber [1,[4][5][6][7]. Consumption of these fruits also positively affects important biomarkers and contributes to a fit physical condition, such as measured in cholesterol parameters [8,9], bone health [10], intestinal microbiota [11], antioxidant status [12] and anthropometrics [13,14]. Furthermore, citrus fruits are beneficial in preventing illnesses, such as cancer [15][16][17], dementia [18], diabetes [19,20], metabolic syndrome [21], and cardiovascular, kidney and dental diseases [17,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In NHANES 2003–2006, higher orange juice consumption was associated with higher daily energy intake in children 4–18 years of age (Wang et al . ).…”
Section: Discussionmentioning
confidence: 97%